Planning, Prices and Increasing Returns - Heal, G. M. (Review of Economic Studies, 1971)
Journal Article Planning, Prices and Increasing Returns Get access G. M. Heal G. M. Heal Christ's College, Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 3, July 1971, Pages 281–294, https://doi.org/10.2307/2296382 Published: 01 July 1971